Exploring students’ mathematical computational thinking ability in solving pythagorean theorem problems - Nurwita, Faizah; Kusumah, Yaya Sukjaya; Priatna, Nanang (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
This study explores students' mathematical computational thinking ability in solving the Pythagorean Theorem problem. This research method used a qualitative approach with a phenomenological design. The subjects involved in this study were 12 junior high school students. Six students in grade 7 had not studied the Pythagorean Theorem, and six students in grade 8 were studying the Pythagorean Theorem. This study's results indicate several problems with students' mathematical computational thinking skills in mathematics learning. The first problem is seen from the aspect of abstraction. Students are given problems with the help of digital-based teaching aids. Then the researcher provides procedures containing questions so students can digest the information and follow their intuition to find a solution strategy. Still, students have not decided what information should be stored or ignored. The second problem is seen from the aspect of decomposition. Students have not been able to decompose complex problems into simpler and more manageable ones. Student responses are also still not according to the researchers' predictions. However, with the scaffolding technique, researchers can direct students' intuition or thought processes to focus more on the problem being asked. The third problem is seen from the aspect of generalization. Students have not been able to generalize the problem and have not been able to conclude from the steps that have been taken. These three problems indicate that students cannot recognize and identify patterns well, thereby reducing the efficiency of the mathematical problem-solving process.